Highly crystalline, pure ZSM-5 from K2CO3-treated mud and its catalytic activity in biodiesel production - Hartati, Hartati; A’yuni, Qurrota; Fitri, Medya Ayunda; Izzah, Adiba Naila; Novitalina, Melinda Intan; Firda, Putri Bintang Dea; Nufus, Tazkiyatun; Prasetyoko, Didik; Harmami, Harmami; Hasliza Bahruji,; Shahrul Nizam Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Addressing the challenge of clean energy and waste management for sustainable development goals, ZSM-5 were synthesized from high-abundance volcano mud (VM) precursor and then utilized as catalyst in biodiesel production. Unlike conventional alkali treatment, we used the reflux method to extract the silica-alumina from the VM. K2CO3 alkali salt was utilized as the extractor, activator, and structure-directing agent. The synthesis was also performed using NaOH as a comparison. Various analytical techniques were employed including XRD, FTIR, SEM-EDX, TEM, N2 physisorption, and GC-MS to identify the effect of alkali types on the crystallization rate, morphology, and catalytic activity. Highly crystalline, pure ZSM-5 was successfully synthesized. It is found that K2CO3 facilitates a slow crystallization rate, requiring a minimum of 5 h of hydrothermal treatment to produce ZSM-5. Interestingly, slow crystallization led to homogeneous ZSM-5 particles with a narrow size distribution and a high mesoporous structure. In contrast, NaOH promoted a faster crystallization rate, producing inhomogeneous ZSM-5 particles size with a dominant microporosity. Two different feedstock qualities i.e., waste cooking oil (WCO) and oleic acid (OA) were used to assess the catalyst’s versatility. Among all zeolites synthesized using K2CO3, ZK6 exhibited the highest activity, with an 85.9% yield and 30% selectivity for FAME in WCO feedstock. In high-quality OA feedstock, ZK6 achieved significantly higher activity of 97.1% yield with 87.6% selectivity for FAME. ZNa6, the comparable sample synthesized with NaOH, achieved a 78.2% yield with 60.4% FAME selectivity in WCO feedstock. A higher catalytic activity of 97.5% yield with 100% selectivity towards FAME was achieved using high-purity OA feedstock.